Corrigendum - Corrigendum (Journal of Social Studies and Education, 2025)
In the article “Harmonization of Customary Law and Islamic Law in the Management of Forbidden Lakes in Village Communities” (Vol. 03 No. 01, 2025: 01–13), the name Dr. Farouq Saber Al-Shibli was incorrectly included as a co-author without his knowledge, contribution, or consent.His name has now been removed from the article PDF, metadata, and indexing.The editorial team sincerely apologizes for this error.